The Influence of Young People on Household Decisions on Energy Efficiency in Latvia - Brakovska Vita; Blumberga Andra (Environmental and Climate Technologies, 2024)
Young people are the future members of the energy communities, who play a role in shaping a climate-responsible society. However, in the context of the geopolitical and economic events of 2022, the awareness of young people in Latvia about energy efficiency issues and the readiness to engage in climate change mitigation processes, as well as the influence of their attitude on the decisions of adult household members in the field of energy efficiency have not been sufficiently studied. The issue is crucial within the framework of the European Green Deal, where various serious games for building energy communities are being developed, and young people are the ones who can influence the decision-making process. The purpose of the study is to provide serious game developers with an insight into young people's knowledge of energy efficiency issues, associations with a climate responsible society, attitudes towards daily habits in the field of energy efficiency, as well as whether climate change issues are discussed in families and whether young people believe that they can influence views and habits of their family members. 71 participants from four contrasting geographical regions in Latvia took part in the study. The study was conducted using qualitative research methods, including questionnaires and interviews. The results have shown that young people in the regions of Latvia are aware of energy efficiency measures, and the answers provide an insight into the various experiences they have had in their households. The research also highlighted negative aspects, such as young people’s unwillingness to strongly support household comfort level reduction in the name of climate change – only a little more than half would be willing to live in cooler rooms. Young people believe that they can influence the attitude and behaviour of other household members in an energy resource management matter. The results of the study lead to the conclusion that more attention should be paid to messages addressed to young people in public spaces, so that they associate themselves as an existing and future part of energy communities. They should be given examples and explanations regarding the importance of their actions in reducing climate change. Developers of serious games are encouraged to integrate aspects related to youth as participants in decision-making into the content of simulation tools, based on the results of the study.